PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP KEMAMPUAN PEMECAHAN MASALAH DI SEMESTER II-B STKIP TAPANULI SELATAN PADANGSIDIMPUAN - siregar, yulia pratiwi (Institut Pendidikan Tapanuli Selatan, 2016)
This study originated from the low ability of mathematical Problem solving skills of student of STKIP Tapanuli Selatan Padangsidimpuan. It is evident from the low result test mathematical problem solving skills of student of several STKIP Tapanuli Selatan Padangsidimpuan. This study aimed to determine the effect STAD toward mathematical problem solving skills students.This research is Quasy Experiment. The population in this study were students of class 2th SMAN 1 STKIP Tapanuli Selatan Padangsidimpuan. Techniques used in sampling is total sampling. The sample in this study were students of class II-B.Research instrument in this study is test the ability of problem solving students. Data were analyzed using mean aquality test that the t test and U test. These result indicate that There is no interaction between early learning approach with the ability to affect studentsâ ability in mathematical problem solving skills